Cell therapy for spinal cord contusion injury: evaluation of the efficacy of cryopreserved human umbilical cord blood mononuclear cells in a preclinical model - S.I. Ryabov; M.A. Zvyagintseva; S.A. Bazanovich; Y.V. Morozova; S.M. Radaev; S.Е. Zuev; M.A. Khvostova; V.A. Karanadze; A.A. Grin; V.A. Smirnov (Хирургия позвоночника)
Objective. To evaluate the effect of systemic application of cryopreserved human umbilical cord blood mononuclear cells (hUCB-MNCs) in the acute period of spinal cord contusion injury (SCI) on the volume of zone of the spinal cord damage using high-field MRI. Material and Methods. This study was performed on adult female Sprague-Dowley rats. Severe contusion SCI was modeled using the weight-drop method. Cryopreserved hUCB-MNC concentrate, stored in a cryobank for 3–4 years at –196 °C, was administered intravenously 1 day after injury. Locomotor behavior was assessed when animals moved in an open field using the BBB (Basso – Beatty – Bresnahan) scale for rats. MRI examination of the spinal cord was performed using a Clin Scan 7.0 T device. Results. At week 6 after injury, a significant increase in the level of restoration of the motor function of the hind limbs (~10 %) was observed in the cell therapy group using hUCB-MNCs relative to the level of the self-healing group (p < 0.05). At the same time, the area of the posttraumatic cystic cavity decreased significantly (~45 %) and statistically significantly (p < 0.05), as well as its transverse (~38%) and longitudinal (~41 %) dimensions. Conclusion. Cryopreserved hUCB-MNCs may be an effective and affordable means of cell therapy for contusion SCI when used in the acute period of injury.